2013
DOI: 10.1038/pr.2013.70
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine inflammation alters cardiopulmonary but not cerebral hemodynamics during open endotracheal tube suction in preterm lambs

Abstract: Background: Intrauterine inflammation adversely affects cardiopulmonary, systemic, and cerebral hemodynamics in preterm neonates, but its impact on responses to endotracheal tube (ETT) suction, known to affect hemodynamics, is unknown. We hypothesized that intrauterine inflammation would alter the cardiopulmonary and cerebral hemodynamic response to open ETT suction in preterm lambs. Methods: Chronically instrumented fetuses received intraamniotic lipopolysaccharide (LPS; to induce intrauterine inflammation) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…This deteriorated oxygenation in the GCSF þ LPS group at 72 hours might be explained as a result of transient pulmonary hypertension induced by severe intrauterine inflammation because there was no deterioration in any of the other respiratory function parameters (VEI, Cdyn, and MAP) in this group that were also expected to reflect the alveolar injury. Pulmonary hypertension after birth following intrauterine inflammation in preterm lambs was also reported by Galinsky et al 33 To our surprise, however, the GCSF þ LPS group showed no significant differences in any of the respiratory function parameters at day 10 of MV, compared to in the other 3 groups, despite the fact that the alveolar surface area per unit volume in this group had decreased by 55% relative to the control group. Although the underlying reason remains unclear, this phenomenon is of profound interest since it is not inconsistent with the fact that the respiratory insufficiency in human preterm infants with Wilson-Mikity syndrome, which is thought to represent new BPD, 34 is not manifested for several days after birth.…”
Section: Discussionsupporting
confidence: 80%
“…This deteriorated oxygenation in the GCSF þ LPS group at 72 hours might be explained as a result of transient pulmonary hypertension induced by severe intrauterine inflammation because there was no deterioration in any of the other respiratory function parameters (VEI, Cdyn, and MAP) in this group that were also expected to reflect the alveolar injury. Pulmonary hypertension after birth following intrauterine inflammation in preterm lambs was also reported by Galinsky et al 33 To our surprise, however, the GCSF þ LPS group showed no significant differences in any of the respiratory function parameters at day 10 of MV, compared to in the other 3 groups, despite the fact that the alveolar surface area per unit volume in this group had decreased by 55% relative to the control group. Although the underlying reason remains unclear, this phenomenon is of profound interest since it is not inconsistent with the fact that the respiratory insufficiency in human preterm infants with Wilson-Mikity syndrome, which is thought to represent new BPD, 34 is not manifested for several days after birth.…”
Section: Discussionsupporting
confidence: 80%
“…Open tracheal suction soon after birth increased PBF, left ventricular output, systemic arterial pressure, and CBF (32). Removal of positive end-expiratory pressure in preterm infants reduced cerebral blood flow velocity in preterm infants with a patent DA, primarily due to increased ductal stealing, evident by negative CBF velocities during diastole (example in Figure 2) (33,34).…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 98%
“…Some practitioners are concerned about possible harmful effects of tracheal suctioning( 19 ) such as vagal stimulation resulting in bradycardia, apnea, tissue trauma and risk of transmitting infection from the mother's secretions from the birth canal( 20 ). A recent study reported increased cerebral and pulmonary blood flow following open endotracheal tube suctioning in preterm lambs( 21 ). Three out of 15 asphyxiated lambs (20%) had cardiac arrest requiring chest compressions with suctioning in the current study (compared to no lambs with cardiac arrest in the no-suction group, p-not significant).…”
Section: Discussionmentioning
confidence: 99%